2012
DOI: 10.1007/s13224-012-0218-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Emergencies: Role of Obstetric Drill for a Better Maternal Outcome

Abstract: Objective To evaluate factors contributing to obstetric emergencies, analyze the fetomaternal outcome and role of obstetric drill in facing these emergencies effectively. Material and Method Out of 10,892 deliveries, a total of 520 women were included in this prospective study. Analysis of emergency obstetric conditions was done by evaluating incidence, various contributing factors, and fetomaternal outcome. Obstetric drill was conducted among residents repetitively. Pre drill and post drill assessment of conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…Reports from studies that have evaluated training programs in India have emphasized the need for dedicated personnel and a trainee tracking system to ensure quality training management and implementation 9 , 17 . They have also showed that strengthening essential supplies and supportive supervision is critical to practice and to retain the newly acquired skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from studies that have evaluated training programs in India have emphasized the need for dedicated personnel and a trainee tracking system to ensure quality training management and implementation 9 , 17 . They have also showed that strengthening essential supplies and supportive supervision is critical to practice and to retain the newly acquired skills.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment recommended improving clinical skills competencies and facility preparedness, especially emergency preparedness through a continuous support mechanism 5 . Recent studies on emergency preparedness have reported that emergency obstetric drills have resulted in improvements in the knowledge and skill levels of providers as well as in facility preparedness 6 9 …”
Section: Introductionmentioning
confidence: 99%
“…1 While most childbirth related complication allows time for proper management, a few present as obstetric emergencies where successful outcome depends on prompt action and systematic rapid management. [1][2][3][4] Obstetric emergencies are defined as situations of serious and often dangerous nature, developing suddenly and unexpectedly and demanding immediate attention in order to save life. [1][2][3][4] These emergencies are not only encountered in perinatal period as post-partum hemorrhage, ruptured uterus, retained placenta, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Obstetric emergencies are defined as situations of serious and often dangerous nature, developing suddenly and unexpectedly and demanding immediate attention in order to save life. [1][2][3][4] These emergencies are not only encountered in perinatal period as post-partum hemorrhage, ruptured uterus, retained placenta, etc. but also in early pregnancy as ruptured ectopic, complications of abortion, antepartum haemorrhage and ante-partum eclampsia all being equally fatal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation